2020
DOI: 10.18865/ed.30.2.321
|View full text |Cite
|
Sign up to set email alerts
|

PRIDE Peer Mentor Development Program: Lessons Learned in Mentoring Racial/Ethnic Minority Faculty

Abstract: Introduction: Mentorship is crucial for academic success. And yet, there are few mentoring programs that address the needs of underrepresented, racially/ethnically diverse junior faculty conducting health-related research in the United States.Methods: To expand mentoring capacity for these racially/ethnically diverse faculty, we developed a Peer Mentor Develop­ment Program (PMDP) to prepare near-peers, who have similar characteristics and personal experiences, to provide support to participants in an NIH-PRIDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The majority of peer mentoring programmes (84%) were in person; all met in small groups, with as few as three per group, 18,25 although two programmes had 9–12 participants per group 12,29 . Most groups met about once a month 12,18,21–23,32 . Slightly more than half (58%) included formal didactics as part of the programme.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of peer mentoring programmes (84%) were in person; all met in small groups, with as few as three per group, 18,25 although two programmes had 9–12 participants per group 12,29 . Most groups met about once a month 12,18,21–23,32 . Slightly more than half (58%) included formal didactics as part of the programme.…”
Section: Resultsmentioning
confidence: 99%
“…Congregating peers can mitigate a hierarchy that may be present in medicine due to differences in academic rank or status. Moreover, several programmes targeted female faculty and/or junior faculty, including one for URMs 21 ; these historically disempowered groups in academic medicine may especially benefit from the formation of peer‐based alliances. For the academic leader aiming to create peer mentoring structures, our second recommendation is to set an intention that aligns with the benefits of peer mentoring, and potentially grouping faculty by similar characteristics to create conducive spaces for career support.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, UR faculty have reported lower perception of inclusion and less satisfaction with the academic diversity climate, networking, and intention to remain at their current institution [14,15]. While several mentoring programs for UR faculty demonstrated improvements in scholar productivity, none examined UR faculty satisfaction with quality of mentoring or their perceptions of the institutional climate [31,38,39]. Professional development programs like NCLAM and HCOE can provide a community of practice and networks for junior faculty to thrive; our data suggest the added benefit of FMTP integrated into established faculty development programs enhances junior faculty engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Peer (or near-peer) mentor development programs offer a great opportunity to train people to be mentors early in their own careers and to expand the pool of mentors. 13,14…”
Section: Retention Of Urm Physician-scientists: Key Issues and Ways T...mentioning
confidence: 99%